Fintech and Financial Inclusion: Legal Opportunities and Barriers - Hasnah Aziz; La Ilman; M. Umar Kelibia; Ide Raunas; Harmoko (Cita Konsultindo Research Center, 2026)
This paper examines the role of financial technology (fintech) in advancing financial inclusion while highlighting the legal opportunities and barriers that shape its development. Fintech has emerged as a transformative force, enabling access to financial services for underserved and unbanked populations through digital platforms, mobile banking, and innovative payment systems. The study explores how regulatory frameworks can facilitate innovation by promoting competition, consumer protection, and financial stability. At the same time, it identifies key legal challenges, including regulatory uncertainty, data privacy concerns, cybersecurity risks, and compliance costs that may hinder fintech expansion, particularly in emerging markets. Using a qualitative approach based on secondary data and comparative legal analysis, this paper evaluates different regulatory models and their effectiveness in balancing innovation with risk mitigation. The findings suggest that adaptive and inclusive legal frameworks are essential to maximize fintech’s potential in promoting equitable financial access. The paper concludes by recommending policy strategies that support innovation while ensuring accountability and trust in digital financial ecosystems.